Advances in research of polysaccharides in Cordyceps species - Zhong, Shi (Array, 2009)
Summary: Cordyceps sinensis (Berk.) Sacc. is one of the well-described fungi that has been used in traditional Chinese medicine for over 700 years. Fungal mycelia contain some polysaccharides that are responsible for their biological activity. C. sinensis has traditionally been cultivated on the high Tibetan plateau as a parasitic fungus growing on caterpillars. However, currently it is being cultivated on some insects and in artificial media. This article deals with the advances in the production, isolation and purification of Cordyceps polysaccharide (CP) in recent years, as well as the structure elucidation and pharmacological action. The article also aims to provide some references for further application and exploitation in the future